2022
DOI: 10.1111/bph.15842
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human recombinant T‐type calcium channels by phytocannabinoids in vitro

Abstract: Background and Purpose: T-type Ca channels (I Ca ) regulate neuronal excitability and contribute to neurotransmitter release. The phytocannabinoids Δ 9 -tetrahydrocannabinol and cannabidiol effectively modulate T-type I Ca , but effects of other biologically active phytocannabinoids on these channels are unknown. We thus investigated the modulation of T-type I Ca by low abundance phytocannabinoids. Experimental Approach: A fluorometric (fluorescence imaging plate reader [FLIPR]) assay was used to investigate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…Our findings that the minor phytocannabinoids CBDVA and CBGVA inhibit T-type calcium channels extend upon research showing that phytocannabinoids and synthetic cannabinoids inhibit these channels ( Ross et al, 2008 ; Mirlohi et al, 2021 , 2022 ). We recently reported that the structurally related phytocannabinoid CBGA, which is also anticonvulsant, inhibited Ca v 3.1 and Ca v 3.2 channels ( Mirlohi et al, 2022 ). Here CBDVA and CBGVA displayed lower potency than CBGA using an identical fluorescent reporter assay.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our findings that the minor phytocannabinoids CBDVA and CBGVA inhibit T-type calcium channels extend upon research showing that phytocannabinoids and synthetic cannabinoids inhibit these channels ( Ross et al, 2008 ; Mirlohi et al, 2021 , 2022 ). We recently reported that the structurally related phytocannabinoid CBGA, which is also anticonvulsant, inhibited Ca v 3.1 and Ca v 3.2 channels ( Mirlohi et al, 2022 ). Here CBDVA and CBGVA displayed lower potency than CBGA using an identical fluorescent reporter assay.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas in this study, CBGVA negatively shifted fast inactivation but not activation, and CBDVA did not affect either state. The preferential shift of the fast inactivation curve in Ca v 3.1 channels by CBGVA is similar to CBD, CBG and CBDV at Ca v 3.1 channels (Ross et al, 2008;Mirlohi et al, 2022). Hyperpolarising shifts of steady-state fast inactivation suggest preferential binding of CBGVA to the inactivated state Frontiers in Pharmacology frontiersin.org of the Ca v 3.1 channels (Freeze et al, 2006;Eckle and Todorovic, 2010).…”
Section: Cbgva and Cbdva Inhibition Of Ca V 31 Is Frequency-dependentmentioning
confidence: 67%
See 2 more Smart Citations
“…Since CBD does not activate CB1 and CB2 receptors, some of the attention in cannabinoid research has recently been focused on CB1 and CB2-independent cellular and molecular targets for CBD and other phytocannabinoids such as cannabigerol and cannabidivarin ( Ghovanloo et al, 2022 ; Isaev et al, 2022 ; Mirlohi et al, 2022 ). In fact, in earlier studies, cannabinoid-receptor independent effects have been described for both endogenous and synthetic cannabinoids as well ( Johnson et al, 1993 ; Fan, 1995 ; Oz et al, 2000 ).…”
Section: Introductionmentioning
confidence: 99%